Biopsychosocial benefits of movement-based complementary and integrative health therapies for patients with chronic conditions. (March 2020) - Bolton, Rendelle E; Fix, Gemmae M; VanDeusen Lukas, Carol; Elwy, A Rani; Bokhour, Barbara G
Objectives: Complementary and integrative health practices are growing in popularity, including use of movement-based therapies such as yoga, tai-chi, and qigong. Movement-based therapies are beneficial for a range of health conditions and are used more frequently by individuals with chronic illness. Yet little is known about how patients with chronic conditions characterize the health benefits of movement-based therapies. Methods: We conducted focus groups with 31 patients enrolled in yoga and qigong programs for chronic conditions at two VA medical centers. Transcripts were analyzed using conventional content analysis with codes developed inductively from the data. Participants' descriptions of health benefits were then mapped to Engel's biopsychosocial model. Results: Participants described improvements in all biopsychosocial realms, including improved physical and mental health, reduced opiate and psychotropic use, enhanced emotional well-being, and better social relationships. Changes were attributed to physical improvements, development of coping skills, and increased self-awareness. Discussion: Patients with chronic illnesses in our sample reported multiple benefits from participation in movement-based therapies, including in physical, mental, and social health realms. Providers treating patients with complex comorbidities may consider referrals to movement-based therapy programs to address multiple concerns simultaneously, particularly among patients seeking alternatives to medication or adjunctive to an opiate reduction strategy.